Disorder- and treatment-specific therapeutic competence scales for posttraumatic stress disorder intervention: development and psychometric properties - Dittmann, Clara; Görg, Nora Saskia; Rausch, Sophie (Journal of traumatic stress, 2017)
Although the assessment of therapeutic competence in psychotherapy research is essential for examining its possible associations with treatment outcomes, it is often neglected due to high costs and a lack of valid instruments. This study aimed to develop two therapeutic competence scales that assess disorder-specific and treatment-specific therapeutic competence, and to examine these scales’ psychometric properties along with those of the already established Cognitive Therapy Scale (CTS) in a posttraumatic stress disorder (PTSD) sample. Using an inductive procedure, two rating scales for assessing disorder-specific and treatment-specific competence were constructed. The psychometric properties of these scales and those of the CTS were assessed in a sample of 30 videotaped sessions of eight patients from a multicenter study in which PTSD related to child abuse was treated using cognitive processing therapy. Two raters assessed therapeutic competence in 30 videotaped psychotherapy sessions. Interrater reliability, internal consistency, and content validity were determined. The scales (all items and total scores) demonstrated good to excellent interrater reliability, intraclass correlation coefficients (ICCs) = .67 to .97, and internal consistency, Cronbach's α = .73 to .92. The PTSD experts’ ratings confirmed good internal validity. We found statistically significant associations with therapeutic adherence, r = .62 to .85; p < .001; and therapeutic alliance, r = .47, p < .001. These preliminary data imply that the two newly developed competence scales and the CTS can be reliably used to assess different types of therapeutic competence in PTSD samples and may be useful as possible predictors of treatment outcomes.